1991
DOI: 10.1557/proc-227-103
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time FT-IR Studies Of The Reaction Kinetics For The Polymerization Of Divinyl Siloxane Bis-Benzocyclobutene Monomers

Abstract: The thermal polymerization reaction of divinyl siloxane bis-benzocyclobutene (DVS bis-BCB) was monitored in-situ with FT-IR spectroscopy in order to follow specific chemical changes and determine the reaction order and rate constants at temperatures from 150° to 210°C. FT-IR spectra were obtained at regular intervals throughout the reaction with a Nicolet 170SX spectrophotometer.Monomeric DVS bis-BCB contains mixed stereo and positional isomers of 1,3- bis(2-bicyclo[4.2.0]octa-1, 3, 5-trien-3-ylethenyl)-1, 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 1 publication
4
20
1
Order By: Relevance
“…The activation energy (E a ) can be calculated from the expression (Ozawa, 1970): where f is the heating rate (8C/min), T is the absolute temperature, R is the gas constant and E a is the activation energy. The activation energy obtained in this study is quite close to the reported value of 36:0^0:9 kcal=mol or 150.7 kJ/mol from real-time FTIR reaction kinetics study (Stokich et al, 1991). Hence, degree of cure predicted by both FTIR and DSC methods should give close correlation.…”
Section: Cumulative Curing Time Studysupporting
confidence: 87%
See 1 more Smart Citation
“…The activation energy (E a ) can be calculated from the expression (Ozawa, 1970): where f is the heating rate (8C/min), T is the absolute temperature, R is the gas constant and E a is the activation energy. The activation energy obtained in this study is quite close to the reported value of 36:0^0:9 kcal=mol or 150.7 kJ/mol from real-time FTIR reaction kinetics study (Stokich et al, 1991). Hence, degree of cure predicted by both FTIR and DSC methods should give close correlation.…”
Section: Cumulative Curing Time Studysupporting
confidence: 87%
“…By quantifying the growth or depletion of these peaks, the extent of cure can be determined. A strong absorption at 1,254 cm 2 1 associated with the rocking mode of the methyl groups attached to the silicon atoms can be used for normalization since these bonds are nearly unaffected by the polymerization (Dow, 1995;Stokich et al, 1991). It has been reported that all FTIR transmission measurements for BCB should be done at Brewster's angle to eliminate interference fringes.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of cure temperature and time have been extensively characterized for BCB resins. 26 The polymerization of BCB proceeds through a two-step thermally activated process with an o-quinodimethane intermediate. 27 The polymerization follows first-order reaction kinetics with an activation energy of 150 kJ/mol.…”
Section: A Specimen Preparationmentioning
confidence: 99%
“…The discrete IR wavelength gets into resonance with the rotation or vibration of some molecule groups. The rate of reactants and products of the polymerization could be estimated by the peak height [15]. The samples were measured before and after the curing by the "FT-IR 2000 System" from Perkin-Elmer.…”
Section: Measurement Of the Polymerization Degree Of Bcbmentioning
confidence: 99%